Phenylalanine, Cysteine, and Sodium Selenate Alleviate Chilling Injury in Cape Gooseberry (Physalis peruviana L.) Seedlings by Enhancing Antioxidant Activities and Membrane Stability - Arezoo Akbari; Taher Barzegar; Vali Rabiei; Silvana Nicola (Horticulturae, 2024)
Low temperature is a major environmental factor that negatively affects the growth and productivity of plants, such as the tropical fruit Cape gooseberry (Physalis peruviana L.), which is susceptible to cold stress. Therefore, to investigate the effect of the amino acid L-phenylalanine (Phe), L-cysteine (Cys), or sodium selenite (Se) on enhancing antioxidant activities, experiments were conducted on the phenolic compounds, proline content, and membrane stability of Cape gooseberry seedlings under low-temperature stress. The seedlings were exposed for 48 h to a low temperature (4 °C) followed by 24 h of optimal growth conditions. In seedlings treated with Se, we found a high relative water content, good membrane integrity, low ion leakage, and hydrogen peroxide. Additionally, this treatment led to the improvement of photosynthetic pigments and antioxidant activity. The analysis of seedlings under cold stress showed that the Phe enhanced the stomatal conductance and phenol content. Furthermore, low concentrations of Cys resulted in the production of proline and flavonoids, which reduced the negative effects of environmental stress on seedlings and maintained cell membrane integrity. Overall, in this experiment, the use of Se and low concentrations of Cys had a positive effect on the amount of antioxidant compounds, which improved seedling growth under stress conditions.